Investigation of mechanical properties and salt spray corrosion test parameters optimization for AA8079 with reinforcement of TiN + ZrO₂ - Sathish, T. (2021)
This work mainly focuses on increasing the mechanical strength and improving the corrosion resistance of an aluminum alloy hybrid matrix. The composites are prepared by the stir casting procedure. For this work, aluminum alloy 8079 is considered as a base material and titanium nitride and zirconium dioxide are utilized as reinforcement particles. Mechanical tests, such as the ultimate tensile strength, wear, salt spray corrosion test and microhardness test, are conducted effectively in the fabricated AA8079/TiN + ZrO₂ composites. L9 OA statistical analysis is executed to optimize the process parameters of the mechanical and corrosion tests. ANOVA analysis defines the contribution and influence of each parameter. In the tensile and wear test, parameters are chosen as % of reinforcement (3%, 6% and 9%), stirring speed (500, 550 and 600 rpm) and stirring time (20, 25 and 30 min). Similarly, in the salt spray test and microhardness test, the selected parameters are: percentage of reinforcement (3%, 6% and 9%), pH value (3, 6 and 9), and hang time (24, 48 and 72 h). The percentage of reinforcement highly influenced the wear and microhardness test, while the stirring time parameter extremely influenced the ultimate tensile strength. From the corrosion test, the hang time influences the corrosion rate. The SEM analysis highly reveals the bonding of each reinforcement particle to the base material.